Future anxiety, depression and stress among undergraduate students: psychological flexibility and emotion regulation as mediators - Öztekin, Gülçin Güler; Gómez-Salgado, Juan; Yıldırım, Murat (Frontiers in Psychology, 2025)
IntroductionMental health and wellbeing are fundamental and integral components of healthy functioning, and psychological resources significantly contribute to its maintenance and enhancement. This study aimed to investigate the mediating effects of psychological flexibility and emotion regulation in the association between future anxiety, depression, and stress.MethodsA total of 528 undergraduate students participated in this study (M = 20.14, SD = 1.76).ResultsThe findings of the study showed that future anxiety was negatively associated with psychological flexibility and cognitive reappraisal, and positively associated with expressive suppression, depression and stress. Psychological flexibility and cognitive reappraisal had negative relationships with depression and stress, and expressive suppression had a positive relationship with depression and stress. The associations between future anxiety, depression and stress were mediated by psychological flexibility, cognitive reappraisal and expressive suppression.DiscussionThis study deepened our understanding of the possible mechanisms of depression and stress. For individuals suffering from future anxiety, psychological flexibility and emotion regulation may be a coping strategy that leads individuals to less depression and stress. This study suggests that psychological flexibility and emotion regulation skills are fundamental aspects of psychological health.